Dose, duration, and cost: opportunities to improve use of long-term oral antibiotics for people with rosacea. (2nd January 2019) - Rill, Joanne S.; Lev-Tov, Hadar; Liu, Guodong; Kirby, Joslyn S.
Abstract: Background: Systemic antibiotics are often used to treat rosacea and tetracyclines are the most common antibiotic prescribed; however, there is ambiguity among clinical guideline suggestions. Importantly, there is an increasing call to all clinicians to curtail antibiotic use. Objective: To investigate the utilization and cost of long-term oral antibiotic use for the treatment of rosacea, including ocular rosacea. Methods: This was a retrospective cohort study of MarketScan ® Commercial Claims and Encounters database, from January 1, 2005 through December 31, 2014. Claim data were used to determine the duration and costs of antibiotic treatment among adults with rosacea. Results: The sample included 72, 411 patients. The mean (SD) duration of long-term antibiotic treatment was 87.68 (145.99) days and for patients with ocular rosacea was slightly longer, 108.34 (176.74) days [ p  < .0001]. The majority of antibiotic courses were shorter than 3 months (80.04%) for the entire sample and the subset with ocular rosacea (53.64% [ p  = .007]). Limitations: Patient adherence is uncertain and database lacks information on rosacea severity and clinical outcomes. Conclusions: The majority of oral antibiotic course durations follow guidelines. Costs of antibiotic therapy were lower for shorter courses and those utilizing generic medications; the cost-effectiveness of these modifications has not been investigated.